ANALISIS TEHADAP PEMANFAATAN FACEBOOK SEBAGAI MEDIA INFORMASI DI PROKOPIM SETDA TANAH DATAR - Rahmad Erlianda (Jurnal Komunikasi, 2024)
The English translation of your text is as follows: "As human civilization evolves, there is a growing effort to advance technology and information for both individual and global interests, one of which is communication tools in the form of the Internet network. This is also undertaken by the Communication and Information Office of the Tanah Datar Regency in utilizing technology as a tool to convey information. The Communication and Information Office of Tanah Datar uses Facebook as a means to disseminate information to the public. This research is conducted to understand the utilization of Facebook and the obstacles in using Facebook as an information medium by the Communication and Information Office of Tanah Datar. This research employs a qualitative descriptive research design. Data collection is carried out through observation, interviews, and documentation. The research informants are the head of the communication and information department. To facilitate understanding of the utilization of Facebook and the obstacles in using Facebook as an information medium by the Communication and Information Office of Tanah Datar, the author employs the theory of new media. Based on the research results, the utilization of Facebook as an information medium by the Communication and Information Office of Tanah Datar includes the use of profile features to make the public aware that the account belongs to the communication and information office, uploading photos and videos to provide information to the public, and using the inbox to respond to messages from the public. The internal obstacle is the lack of optimization of the reels feature on Facebook, busy schedules, and external obstacles such as slow internet network